THE EFFECT OF THE PROBLEM BASED LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN ECONOMICS SUBJECTS AT SMA NEGERI 2 INDRALAYA UTARA - Adelia, Yosica; Fatimah, Siti (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study aims to prove the influence of the Problem Based Learning model on students learning outcomes in economics subjects at SMA Negeri 2 Indralaya Utara. Quantitative research methods of experimental type with quasi-experimental research methods. The population in this study is class XI of SMA Negeri 2 Indralaya Utara even semester of the 2024/2025 academic year. The research sample of class XI.2 totaling 25 students using the Cluster Sampling technique. The data collection techniques used are tests and observations. The test is used to obtain learning outcome data and observation data obtained from observation results during the treatment of the Problem Based Learning model during the learning process. The hypothesis test was carried out using a paired sample t-test showing that tcount 6.137> ttable 1.710 meaning that Ho was rejected and Ha was accepted so that it can be concluded that there is an influence of the Problem Based Learning model on the learning outcomes of students in economics subjects at SMA Negeri 2 Indralaya Utara. It is recommended that students can better understand and improve learning outcomes, so that the results obtained can be increased through active learning